Assessment of myocardial function and cardiac performance using left ventricular global longitudinal strain in athletes after COVID-19: a follow-up study - Schellenberg, J.; Matits, L.; Bizjak, D. A.; Kersten, J.; Kirsten, J.; Vollrath, S.; Steinacker, J. M. (Frontiers in Cardiovascular Medicine, 2023)
Background It has not yet been conclusively determined whether reduced left ventricular global longitudinal strain (LV GLS) after COVID-19 contributes to a reduction in exercise capacity. Our own studies showed a possible mild myocardial involvement in the form of reduced LV GLS in athletes after COVID-19 compared with healthy athletes. The aims of this prospective follow-up study were to investigate the development of LV GLS over a 3-month period in athletes after COVID-19 and the possible relationship between LV GLS and physical performance. Methods LV GLS was determined in four-, two-, and three-chamber views and assessed offline by a blinded investigator in 96 recreational athletes (mean age 33.15 ± 12.40 years, 53 male, peak VO2 38.82 ± 11.14 ml/min/kg) at a median of two (t0) and five months (t1) after COVID-19. Cardiopulmonary exercise testing (CPET) was performed on a bicycle ergometer on both examination dates. Results LV GLS improved significantly between t0 and t1 (t0 −18.82 ± 2.02 vs. t1 −19.46 ± 2.05, p < 0.001). Echocardiographic and spiroergometric parameters were within the normal clinical reference range. Maximum power increased significantly from t0 to t1 (t0 283.17 ± 83.20 vs. t1 286.24 ± 85.22 Watt, p = 0.009) and there was a trend toward increased peak oxygen uptake (t0 36.82 ± 11.14 vs. t1 38.68 ± 10.26 ml/min/kg, p = 0.069). We found no correlation between LV GLS and performance parameters, except for the respiratory exchange ratio (RER) [ρ −0.316, (−0.501; −0.102), p < 0.050]. Conclusions Significant improvement in LV GLS approximately five months after COVID-19 may be due to mild myocardial involvement during or shortly after COVID-19, which seems to recover. There was no correlation between LV GLS and performance parameters, except for an inverse correlation of LV GLS and RER, suggesting insufficient exercise intolerance at lower GLS values. Further studies on the development of GLS in athletes or in the general population with moderate and severe disease courses would be informative as well as the comparison of pre-COVID-19 with post-COVID-19 echocardiography to evaluate the effects of COVID-19 on cardiac function.